(untitled) (Agro Productividad, 2022)
Objective: To quantify the direct and indirect damage caused by Diceroprocta bulgara in lime cultivars: Persian, Mexican with and without thorns, Colimex and Lise; on the Coast of Oaxaca, Mexico. Design/Methodology/Approach: The damage caused by D. bulgara was calculated by counting nests in trees of five lime cultivars (Persian, Mexican with thorns, Mexican without thorns, Colimex and Lise). In each plot, 15 trees were selected randomly to evaluate the variables: height, crown diameter, damaged growth flows, damaged growth diameter, damage length, and number of eggs. The loss of fruit from the indirect effect (kg ha-1), was estimated in three densities of Colimex and Lise. Results: The damage ranged between 78.6% (Mexican without thorns) and 94% (Colimex). The trees of largest size showed a higher percentage of affected flows. The second flow showed the highest frequency of damage (32%), while the lowest frequency was obtained in the first flow (17.3%). The lowest number of eggs was 26 in flow one in Mexican lime without thorns, while the highest was 171 in Mexican lime without thorns. The greatest number of eggs was observed in Persian lime (371). A significant relationship was determined between the number of eggs and the damage length and flow diameter (<0.05). The highest number of mummified fruits (15.6) was observed in Colimex (density of 312 trees ha-1) and the estimation that up to 146 kg of fruit could be lost. Findings/Conclusions: This study quantifies for the first time the direct and indirect damage caused by oviposition of the cicada D. bulgara, which represents a loss of fruit in productive trees. Studies on the insect’s biology are suggested for integral management plans.